INFLUENCE OF DRAINAGE WELLS IN ANTIFILTRATION DRAINAGE SYSTEM - Levytska, V.; Khoruzhiy, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The decrease of water levels in the drainage wells of the coastal anti-filtration drainage system with the siphon method of water intake from them was analyzed. The interaction of water-lowering wells with different depths and located at variable distances from each other is considered, which makes it possible to ensure uniform drainage from each well and to achieve a steady decrease in the level of groundwater over the entire length of the antifiltration drainage system.The results of the performed analytical studies are presented. The example of the Kamyanka-Dniprovska's anti-filtration drainage system shows that the decrease in water levels in wells at the same flow rate of pumped water depends on their hydraulic interaction, hydrogeological conditions of water filtration from the aquifer and the distance of the antifiltration drainage system from the bank-side. The results obtained indicate that the highest level of water depletion of the coastal vertical anti-filtration drainage system line with siphon drainage from wells is achieved at a distance of a number of wells from the Kakhovsky reservoir bank-side a = 100 m, at the same water flow rate from each of the drainage wells (Q = 604,8 m3 /day), located at different distances from each other. The highest rate of additional reduction of water obtained through mutual hydraulic action was obtained in the 7th well, which has a depth of 14,9 m, and it is located at a distance of 100 m from the 6th well and at a distance of 110 m from the 8th well. The lowest indicator of the level of groundwater reductions at different indicators of the distance of a number of drainage wells to the bank-sideа (30, 50, 80, 100 m) is observed in the first well, farthest from the water collection well.
Keywords: anti-filtration drainage system; drainage wells; siphon method of water intake; water depletion; aquifer; Kakhovsky reservoir; level of groundwater reduction